Raymond Poincaré - Keiger, John F. V. (Cambridge University Press, 1997)
This study is a scholarly biography of one of France's foremost political leaders. In a career which ran from the 1880s to the 1930s, one of the most formative periods of modern French history, Poincaré held the principal offices of state. He played crucial roles in France's entry into the Great War, the organisation of the war effort, the peace settlement, the reparations question, the occupation of the Ruhr and the reorganisation of French finances in the 1920s. His life and work is surrounded by controversy and myth, from 'Poincaré-la-guerre' to 'Poincaré-le-franc', which this book dissects. Using a host of new archival material, Professor Keiger explores the historiography of the man and his times and reveals, somewhat surprisingly, how animal rights and feminism could be as important to him as party politics and public finance.